To bounce or not to bounce in generalized Proca theory and beyond - Lara Bohnenblust; Serena Giardino; Lavinia Heisenberg; Nadine Nussbaumer (Journal of High Energy Physics)
Abstract It is notoriously difficult to construct a stable non-singular bouncing cosmology that avoids all possible instabilities throughout the entire evolution of the universe. In this work, we explore whether a non-singular bounce driven by a specific class of modifications of General Relativity, the vector-tensor generalized Proca theories, can be constructed without encountering any pathologies in linear perturbation theory. We find that such models unavoidably lead either to strong coupling in the tensor or the scalar sector, or instabilities in the matter sector during the bouncing phase. As our analysis is performed in a gauge-independent way, this result can be cast in the form of a no-go theorem for non-singular bounces with generalized Proca. In contrast to the no-go theorem found for Horndeski theories, however, it cannot be evaded by considering beyond generalized Proca theory. At the core of our result lies the non-dynamical nature of the temporal component of the vector field, which renders it an ill-suited mediator for a bouncing solution.